AIDS-related Stigma, HIV Testing, and Transmission Risk Among Patrons of Informal Drinking Places in Cape Town, South Africa - Pitpitan, Eileen V. (2012)
BACKGROUND: AIDS-related stigma as a barrier to HIV testing has not been examined within the context of high at-risk environments such as drinking venues. Of particular importance is whether AIDS-related stigma is associated with HIV transmission risks among people who have never been tested for HIV. PURPOSE: We examined: 1) AIDS-related stigma as a barrier to testing, controlling for other potential barriers, and 2) whether stigma is associated with HIV risks among HIV-untested individuals. METHODS: We surveyed 2,572 individuals attending informal drinking establishments in Cape Town, South Africa to assess HIV testing status, AIDS-related stigma endorsement, and HIV transmission sexual risk behavior. RESULTS: Endorsement of AIDS-related stigma was negatively associated with HIV lifetime testing. In addition, stigma endorsement was associated with higher HIV transmission risks. CONCLUSIONS: AIDS-related stigma must be addressed in HIV prevention campaigns across South Africa. Anti-stigma messages should be integrated with risk reduction counseling and testing.